Environmental sustainability practices in rural libraries / Siti Khadijah Rafie ... [et al.] - Rafie, Siti Khadijah; Abu, Roziya; Sheikh Abdul, Siti Khairunnisa; Samsudin Mutalib, Ahmad Zam Hariro (Universiti Teknologi MARA Cawangan Sarawak, 2021)
The key purpose of this study was to investigate the implementation of environmental sustainability practices in Malaysian rural libraries. A qualitative approach was employed through interviews, observations, and examinations of documents related to the six (6) rural libraries which were involved in this study. This study concluded that rural libraries in Malaysia had not fully implemented the environmental sustainability elements as suggested by the International Federation of Library Association (IFLA). Nevertheless, rural libraries in Malaysia had put good effort into environmental sustainability practices.